Protocellular Materials: A Floating Mold Technique for the Programmed Assembly of Protocells into Protocellular Materials Capable of Non‐Equilibrium Biochemical Sensing (Adv. Mater. 24/2021). Issue 24 (18th June 2021) - Galanti, Agostino; Moreno‐Tortolero, Rafael O.; Azad, Raihan; Cross, Stephen; Davis, Sean; Gobbo, Pierangelo
Abstract : The fabrication of tissue‐like materials capable of emergent bioinspired behaviors represents an emerging challenge of bottom‐up synthetic biology and biomimetic materials science. In article number 2100340, Pierangelo Gobbo and co‐workers report a new technique for the assembly of tissue‐like materials from protocell building blocks. The resulting "protocellular materials" are free‐standing, robust, and can be chemically programmed to display an emergent non‐equilibrium spatiotemporal sensing behavior.